Die Verfassungsmäßigkeit des Onlinezugangsgesetzes - Zäper, Maximilian (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The subject of this work is the reform of administrative digitization by the OZG. At its center is the digi-tization and linking obligation of § 1 OZG: The simple legal form of the "portal association" is analyzed and the defining concept of "administrative service" is interpreted. Based on the addressees of the OZG, the constitutional admissibility is examined. Here, the newly created Article 91c (5) of the Basic Law is placed at the center of consideration and its impact on the federal-state relationship is presented. In addition, the authorizations to issue ordinances, the disclosure under Section 9 of the OZG and the data protection cockpit are analyzed and placed in their administrative and constitutional context.